PROBLEMATIKA KENAKALAN ANAK REMAJA DI KOTA SAMARINDA DITINJAU BERDASARKAN UNDANG-UNDANG NOMOR 17 TAHUN 2016 TENTANG PERLINDUNGAN ANAK - Ayu Abna Sari (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
ABSTRACTChildren are an inseparable part of the continuity of human life and the sustainability of a nation and state. In order to be able to be responsible for the sustainability of the nation and state.Basically, juvenile delinquency is a form of adolescent behavior that is not in accordance with the applicable rules in society, or it can also be said that juvenile delinquency is a form of deviant behavior and the causative factor is due to parental divorce, due to economic factors and so on.Efforts made in minimizing adolescent delinquency are by increasing socialization activities about juvenile deviant crimes, both regarding the dangers, legal consequences, and other things so that adolescents can avoid actions that are against the law. Keywords: Legal Efforts to Handle Juvenile Delinquency